Fast and Female (2007)
Fast and Female is the beginning of a revolution. In 2005, riding high on Canadian World Cup fever and Olympic dreams, the women of Canada`s National Cross Country Ski Team were inspired to share their enthusiasm with the next generation Canadian female cross- country skiers. The program was designed to get more girls skiing, as well as to make a difference in the state of fitness among today`s kids.